A Systematic Literature Review: Integration of Project-Based Learning, Entrepreneurship, and Ethnoscience in Science Education - Dewi Juita; yulkifli; yerimadesi; Muhyiatul Fadhillah; festiyed; asrizal; Yusmaridi M (Indonesian Journal of Science and Education, 2026)
This study systematically reviews the integration of Project-Based Learning (PjBL), entrepreneurship, and ethnoscience in science education as a transformative 21st-century learning framework that connects scientific inquiry, cultural values, and entrepreneurial competencies. Although these concepts have been widely examined separately, studies that integrate all three remain limited. This study employed a Systematic Literature Review (SLR) approach guided by the PRISMA framework to ensure transparency and methodological rigor. Data were retrieved from the Scopus database, yielding 263 initial articles. After applying inclusion and exclusion criteria, 12 relevant articles published between 2022 and 2025 were selected for final analysis. The findings indicate that PjBL functions as a central pedagogical bridge connecting entrepreneurship and ethnoscience by promoting contextual, culture-based, and product-oriented science learning. The reviewed studies were dominated by quasi-experimental and Research and Development (R&D) designs. The most frequently targeted competency was entrepreneurship (44%), followed by critical thinking (17%) and cultural character (11%). Based on these findings, this study proposes an Ethnoscience-Based Project-Based Entrepreneurship Learning (PBEL) model to strengthen students’ creativity, collaboration, innovation, and cultural awareness. The proposed model offers a promising framework for advancing science education that is locally grounded, competence-oriented, and responsive to 21st-century learning demands.